2000
DOI: 10.1002/(sici)1097-4628(20000222)75:8<1083::aid-app13>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular size and aggregation behavior of Erwinia gum in aqueous solution

Abstract: Erwinia (E) gum, a stabilizer and thickening agent of food, is composed of glucose, fucose, galactose, and glucuronic acid (1 : 0.1 : 0.05 : 0.3 by molar ratio). The apparent weight-average molecular weight M w and intrinsic viscosity [] in 0.2 M NaCl aqueous solution were measured to be 7.83 ϫ 10 5 and 268 mL g Ϫ1 , respectively, by light scattering and viscometry. The aggregation behavior of E gum in aqueous solution was investigated by gel permeation chromatography (GPC) and dynamic light scattering. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…This indicates that the E gum formed aggregates in the aqueous solution and that the aggregates were decomposed gradually with increasing temperature, similar to the results of dynamic light scattering. 21 Figures 8 and 9 show that w ag and M w , respectively, of the aggregates of E-3 in a 0.2 M NaCl aqueous solution decreased with an increase in temperature. Obviously, the decrease of w ag and M w of the aggregates resulted in the decrease of the apparent M w of the E gum in the 0.2 M aque- whereas the decrease of M w means a decrease in N ap .…”
Section: Dependence Of Aggregation On Concentrationmentioning
confidence: 97%
See 2 more Smart Citations
“…This indicates that the E gum formed aggregates in the aqueous solution and that the aggregates were decomposed gradually with increasing temperature, similar to the results of dynamic light scattering. 21 Figures 8 and 9 show that w ag and M w , respectively, of the aggregates of E-3 in a 0.2 M NaCl aqueous solution decreased with an increase in temperature. Obviously, the decrease of w ag and M w of the aggregates resulted in the decrease of the apparent M w of the E gum in the 0.2 M aque- whereas the decrease of M w means a decrease in N ap .…”
Section: Dependence Of Aggregation On Concentrationmentioning
confidence: 97%
“…E gum is composed of glucose, fucose, galactose, and glucuronic acid (in a 1/0.1/0.05/0.3 molar ratio). 21,23 The E-gum aqueous solution (0.4 wt %) was centrifuged at 7000 rpm for 12 h to remove the waterinsoluble gum, was then concentrated by rotary evaporation at reduced pressure and room temperature, and was finally precipitated by acetone. The E-gum precipitate was washed eight times with acetone and then vacuum-dried for 7 days to obtain a white powder.…”
Section: Materials and Solution Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The heating could break the aggregates into single chains. 24,27,31 This phenomenon indicated that once the aggregates of A gum decomposed at relatively higher temperatures, they hardly reaggregated at 25°C, suggesting that the aggregation was thermally irreversible. Therefore, the A-gum solution that was heated to 90°C into disaggregates could keep the disaggregation state at room temperature.…”
Section: Dependence Of Disaggregation On Temperaturementioning
confidence: 99%
“…25 E gum, an heteropolysaccharide acid produced by Erwinia mituyensis 5796, 26 is aggregated in a 0.2 M NaCl aqueous solution at low temperatures and is broken up at high temperatures. 24,27 Moreover, E gum in water exhibits an exceedingly high viscosity similar to that of xanthan, a viscosity-enhancing agent. 28 Therefore, clarifying the mechanism of aggregation and disaggregation and the affecting factors is essential for successful applications in food, oil drilling, pharmaceuticals, environment protection, and so on.…”
Section: Introductionmentioning
confidence: 99%